Renewable resources and energy management : proceedings of the International Conference on Innovation in Energy Management & Renewable Resources (IEMRE 2022) /: proceedings of the International Conference on Innovation in Energy Management & Renewable Resources (IEMRE 2022). (2023) - Unknown
No abstract available